A CONNECTION BETWEEN CATEGORIES OF (FUZZY) MULTIALGEBRAS AND (FUZZY) ALGEBRAS - Ameri, R.; Nozari, T. (Italian Journal of Pure and Applied Mathematics, 2010)
The purpose of this paper is study the relationship between the categories of fuzzy multialgebras and crisp algebras. In this regards first we briefly study the categories of multialgebras and fuzzy multialgebras and then by using the fundamental relation of multialgebras we construct a functor from category of fuzzy multialgebras to the category of fuzzy algebras and hence. Hence it can be derived a fuzzy algebra from every fuzzy multialgebras through the fundamental relation.